Lezioni di ingegneria del vento - Pastò, Stefano (Manuali - Scienze Tecnologiche, 2006)
The new multidisciplinary study area of Wind Engineering was born as a response to the needs of design and construction for increasingly daring infrastructures: lighter materials and dimensions have made many projects very sensitive to the action of wind and therefore it is now necessary to study the applied fluid-dynamics, aero-dynamics of bodies and aero-elastics also for the civil engineering sector. The volume is a first attempt at an organic and complete collection of notions at the advanced university course level (including Masters and Doctorates), but it also intends to offer important help to those professionals whose activity is carried out in the design, management and development of works of large dimensions that are sensitive to the action of wind.